Aligning English Instruction with Workplace Communication: ‎A Needs Analysis of Vocational High School Students - Nurhidaya; Badeni; Kasmaini (Yayasan Darussalam Bengkulu, 2025)
This study investigates the English learning needs of vocational high school students to inform workplace-relevant English instruction. A descriptive needs analysis design was employed, involving 75 Grade X students from the Office Management and Business Services (MPLB) program at an Indonesian vocational high school. Data were collected using a 25-item structured questionnaire measuring five dimensions: the importance of English skills, needs for improvement, workplace communication competencies, preferred learning activities, and learning expectations, supplemented by semi-structured interviews. Descriptive statistics and qualitative thematic analysis were applied. The findings reveal strong student agreement (mean > 4.0 on a 5-point scale) on the importance of English for future careers, with speaking and listening identified as the most critical workplace skills. Students strongly prefer interactive activities such as role plays, simulations, group discussions, and project-based learning over traditional grammar exercises. The novelty lies in the comprehensive 25-item needs analysis instrument specifically designed for the MPLB program, offering fresh empirical insights beyond general English curricula. Practically, English teachers and curriculum developers should integrate vocationally relevant, interactive tasks into instruction to bridge classroom learning and workplace demands. The study contributes to the English for Vocational Purposes (EVP) literature by providing a validated needs-analysis framework that demonstrates how learner-centered data can directly guide instructional design aligned with real-world communication requirements.